2018
DOI: 10.1371/journal.pone.0189883
|View full text |Cite
|
Sign up to set email alerts
|

Endothiodon cf. bathystoma (Synapsida: Dicynodontia) bony labyrinth anatomy, variation and body mass estimates

Abstract: The semicircular canal (SC) system of the inner ear detects head angular accelerations and is essential for navigation and spatial awareness in vertebrates. Because the bony labyrinth encloses the membranous labyrinth SCs, it can be used as a proxy for animal behavior. The bony labyrinth of dicynodonts, a clade of herbivorous non-mammalian synapsids, has only been described in a handful of individuals and remains particularly obscure. Here we describe the bony labyrinth anatomy of three Endothiodon cf. bathyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 53 publications
1
27
0
Order By: Relevance
“…Different from what is usually the case in non-mammalian therapsids and mammals, in which the anterior semicircular is the longest (e.g., Olson, 1944;Sigogneau, 1974;Luo, 2001;Kielan-Jaworowska et al, 2004;Rodrigues et al, 2013;Laaß, 2016;Araújo et al, 2017Araújo et al, , 2018Benoit et al, 2017b,c;Bendel et al, 2018;Pusch et al, 2019), the lateral semicircular canal appears to be the longest of the three semicircular canals in Lycosuchus. Several studies have shown that the elongated morphology of the semicircular canals can be linked to the animals' lifestyle (e.g., Spoor, 2003;Spoor et al, 2007;Walsh et al, 2009;Wittmer and Ridgely, 2009;Cox and Jeffery, 2010;Laaß, 2015a;Araújo et al, 2018). The anomodont Kawingasaurus is the only other non-mammalian therapsid described with a lateral semicircular canal larger than the anterior and posterior one, but it was suggested that its elongated morphology is related to the inflated geometry of the vestibule rather than its locomotory behavior (Laaß, 2015a).…”
Section: Variation In Bony Labyrinth Morphology In Therapsidsmentioning
confidence: 85%
See 3 more Smart Citations
“…Different from what is usually the case in non-mammalian therapsids and mammals, in which the anterior semicircular is the longest (e.g., Olson, 1944;Sigogneau, 1974;Luo, 2001;Kielan-Jaworowska et al, 2004;Rodrigues et al, 2013;Laaß, 2016;Araújo et al, 2017Araújo et al, , 2018Benoit et al, 2017b,c;Bendel et al, 2018;Pusch et al, 2019), the lateral semicircular canal appears to be the longest of the three semicircular canals in Lycosuchus. Several studies have shown that the elongated morphology of the semicircular canals can be linked to the animals' lifestyle (e.g., Spoor, 2003;Spoor et al, 2007;Walsh et al, 2009;Wittmer and Ridgely, 2009;Cox and Jeffery, 2010;Laaß, 2015a;Araújo et al, 2018). The anomodont Kawingasaurus is the only other non-mammalian therapsid described with a lateral semicircular canal larger than the anterior and posterior one, but it was suggested that its elongated morphology is related to the inflated geometry of the vestibule rather than its locomotory behavior (Laaß, 2015a).…”
Section: Variation In Bony Labyrinth Morphology In Therapsidsmentioning
confidence: 85%
“…Among therapsids, a lateral semicircular canal larger than the anterior and posterior one has only previously been reported for the fossorial anomodont Kawingasaurus fossilis (Laaß, 2015a). The lateral and posterior canal share a secondary crus commune (Figure 11B), as in most non-mammalian therapsids (e.g., Olson, 1944;Sigogneau, 1974;Castanhinha et al, 2013;Rodrigues et al, 2013;Laaß, 2015aLaaß, , 2016Araújo et al, 2017Araújo et al, , 2018Benoit et al, 2017b,c;Bendel et al, 2018;Pusch et al, 2019). The curved vestibule has a length of 13.59 mm and is surrounded by the opisthotic and the prootic, of which the opisthotic constitutes its posterior and lateral border and the prootic its anterior border.…”
Section: Inner Earmentioning
confidence: 89%
See 2 more Smart Citations
“…The bony labyrinth of Endothiodon cf. E. bathystoma was reconstructed by Ara ujo et al (2018), and the work of Benoit et al (2018) compared the facial innervation of members of Anomodontia, the more inclusive clade containing dicynodonts and their closest relatives.…”
Section: Introductionmentioning
confidence: 99%